Corrosion protection of Mg‐SiC nanocomposite through plasma electrolytic oxidation coating process. Issue 11 (28th June 2022) - Golhin, Ali P.; Kamrani, Sepideh; Fleck, Claudia; Ghasemi, Alireza
Abstract: Understanding the role of nanoparticles in magnesium (Mg)‐based materials and protective coating provides valuable information to achieve an optimized combination of mechanical and corrosion protection properties of Mg nanocomposites. The present study investigates the effects of SiC nanoparticles on the corrosion behavior and structure of Mg‐SiC composites substrates coated by plasma electrolytic oxidation (PEO). Moreover, the influence of different volume fractions of SiCn up to 10% on corrosion behavior and galvanic reactions between Mg matrix and SiC particles was also investigated. The morphology, distribution of the phases, and the microstructure of the coating were characterized by SEM, EDAX, X‐ray photoelectron spectroscopy, and XRD. The corrosion resistance of the samples was determined through dynamic polarization and electrochemical impedance spectroscopy tests before and after PEO coating treatment. The results indicate that the Mg nanocomposite with 1 vol% SiCn (M1Sn) coated by PEO coating shows higher corrosion resistance than the samples with a higher percentage of SiCn, as well as the sample without SiCn particles. Abstract : The presence of SiCn nanoparticles up to a specific amount influences positively the coating formation process and corrosion behavior of the magnesium (Mg) substrate coated with the plasma electrolytic oxidation (PEO) oxide layer. A higher percentage of the SiC nanoparticles in the substrate leads to the formation of a thinner coating layer, which is more porous and contains more microcracks. This deteriorates the corrosion performance of the PEO coating which forms on the Mg nanocomposite.